2009
DOI: 10.1021/ja904307n
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Catalytic Activity and Dynamics of Gold Nanoparticles at the Single-Molecule Level

Abstract: Nanoparticles are important catalysts for petroleum processing, energy conversion, and pollutant removal. As compared to their bulk counterparts, their often superior or new catalytic properties result from their nanometer size, which gives them increased surface-to-volume ratios and chemical potentials. The size of nanoparticles is thus pivotal for their catalytic properties. Here, we use single-molecule fluorescence microscopy to study the size-dependent catalytic activity and dynamics of spherical Au-nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
477
10
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 535 publications
(515 citation statements)
references
References 66 publications
25
477
10
3
Order By: Relevance
“…1. However, numerous studies have shown that gold is not as inert as its d 10 configuration suggests which accounts for its pronounced catalytic and electrocatalytic activity [6,[17][18][19][20][21][22][23][24]. This has been attributed to active sites on the surface that consists of atoms or clusters of atoms that have low co-ordination number and have the ability to partake in electrocatalytic reactions [21,22,25,26].…”
Section: Resultsmentioning
confidence: 99%
“…1. However, numerous studies have shown that gold is not as inert as its d 10 configuration suggests which accounts for its pronounced catalytic and electrocatalytic activity [6,[17][18][19][20][21][22][23][24]. This has been attributed to active sites on the surface that consists of atoms or clusters of atoms that have low co-ordination number and have the ability to partake in electrocatalytic reactions [21,22,25,26].…”
Section: Resultsmentioning
confidence: 99%
“…According to the theory that antifungal activity is size-dependent [82,83], we expected to find activity from the small particles in the AuNP sample. The antifungal activity was evaluated by two different methods; microdilution assay and spot plating assay.…”
Section: Microdilution and Plate Spottingmentioning
confidence: 99%
“…The catalyst they prepared consisted of gold dispersed as nanoparticles on a support, and the high catalytic activity was attributed to the small particle size of Au [14]. Compared to their bulk counterparts, gold nanoparticles (GNPs) often exhibit outstanding catalytic properties resulting from their nanometer size, which gives them increased surface-to-volume ratios and chemical potentials [15]. Following the pioneering study of Haruta, there has been significant research undertaken, and encouraging results have been reported on the application of GNPs to the removal of toxic components from automotive emissions.…”
Section: Catalytic Conversion Of Pollutants In Automobile Emissions Umentioning
confidence: 99%